Preparation of hybrid CuO/TiO₂ photocatalyst responsive toward UV-Light (effect of Cu Concentration): article - Azman, Nur Aifaa; Lim, Ying Pei; Lim, Ying Chin (2017)
The objectives of this research is to prepare hybrid CuO/TiO2 using wet impregnation method by varying copper concentration, to characterize the photocatalyst using XRD, EDX, FESEM and BET and to evaluate the photocatalytic removal of methyl orange by hybrid CuO/TiO2 photocatalyst. To investigate the removal efficiency of methyl orange by using hybrid CuO/TiO2, the copper concentration was varied from 0.3 wt%, to 1.0 wt%. Results showed that 0.5wt% CuO/TiO2 performance was the highest with 46% removal of methyl orange. The kinetic data studies were fitted into pseudo-first, pseudo-second and intraparticle diffusion model. The kinetic of adsorption model was found to follow pseudo-first order model as the regression value at 0.5 wt% copper loading was 91%.